Respostas
respondido por:
13
Valor de y: y = 3x-8. y = 3(0)-8. y = -8. Valor de x: y = 3x - 8. 0 = 3x - 8. 3x = 8. x = 8/3
respondido por:
11
y = 3x - 8
y = 4 - x
=> - x = y - 4
=> x = 4 - y
y = 3(4 - y) - 8
y = 12 - 3y - 8
4y = 4
y = 1
x = 4 - y
=> x = 4 - 1
=>x = 3
x = 3, y = 1
y = 4 - x
=> - x = y - 4
=> x = 4 - y
y = 3(4 - y) - 8
y = 12 - 3y - 8
4y = 4
y = 1
x = 4 - y
=> x = 4 - 1
=>x = 3
x = 3, y = 1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás